PERBAIKAN POLA TANAM PALAWIJA PADA LAHAN KERING DI KABUPATEN PARIGI MOUTONG SULAWESI TENGAH - Syafruddin ,; Irwan Suluk Padang; Saidah , (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2015)
ABSTRACT Improving Crop Rotation in Dryland at Parigi Moutong, Central Sulawesi. Dryland is a fragile natural resource and becomes a challenge in gaining food self-sufficiency, especially in maize, soybean and peanut. Crop rotation provides opportunities to increase crops and land’s productivity. This research aimed to find out the new varieties which are adaptable to dryland, and to examine the best crop rotation of three main crops as well as the feasibilty of farming system di dryland. The research had been conducted for two years (2013-2014) in a three hectares area, devided into two experimental stages. In the first year, the experiment was conducted to find out the adaptable varieties. The experimental design for the first experiment was splite plot design putting the crops as the main plot (maize, peanut and soybean). The splite plot consisted of three varieties from each crop, as follow: Tuban, Bison and existing varieties for peanut; Lamuru, Srikandi Kuning, and existing varities for maize; Argomulyo, Grobongan and existing varieties for soybean. In the second year, the experiment was to improve crops rotation, analysed by BC ratio for four different rotations, which were: 1) Maize-peanut; 2) Peanut-soybean; 3) Maize-soybean; 4) Common crops rotation practiced by local farmers using the existing varieties. The results showed that Tuban variety for peanut, Srikandi Kuning variety for maize and Grobongan variety for soybean were more adaptable compared to other varieties. Crops rotation that produced the highest production and the best income were peanut-maize with B/C 2.04 and 11, respectively, with MBCR 4.95; followed by peanut-peanut with B/C 2.04 and 1.59, respectively, with MBCR 6.71 and the increase in farmers’ income at about 66.50% and 21.0% higher compared to existing farming system. Keywords: Dryland, superior variety,crop rottion and incameABSTRAKLahan kering merupakan sumberdaya alam yang tergolong fragil dan menjadi tantangan dalam pengembangannya untuk pencapaian swasembada pangan, khususnya jagung, kedelai dan kacang tanah. Pola tanam merupakan salah satu alternatif dalam meningkatkan produktivitas lahan dan tanaman. Penelitian ini bertujuan untuk mengetahui pola tanam yang optimal dan kelayakan usahatani pada lahan kering. Penelitian dilaksanakan selama 2 (dua) tahun yaitu 2013-2014 dengan luasan 3 (tiga) ha. Tahun pertama bertujuan untuk mengetahui tingkat adaptasi varietas unggul baru tiga macam tanaman pangan. Rancangan yang digunakan adalah rancangan petak terpisah dengan 3 (tiga) ulangan. Sebagai petak utama adalah tiga jenis palawija: (jagung, kacang tanah dan kedelai). Anak petak terdiri dari tiga varietas dari masing-masing jenis palawija yaitu: 1) kacang tanah meliputi varietas Tuban, Bison dan eksisting, 2) Jagung: Lamuru, Srikandi Kuning dan eksisiting dan 3). Kedelai: argomulyo, grobongan dan eksiting. Pada tahun ke dua perlakuan yang diuji adalah perbaikan pola tanam terdiri atas: 1) Pola tanam jagung - kacang tanah, 2) Kacang tanah – kacang tanah 3) Pola tanam jagung - kedelai dan 4) Pola tanam petani di analisis menggunakan B/C dan MBCR pada masing-masing pola tanam. Hasil yang diperoleh menunjukkan bahwa kacang tanah varietas Tuban, jagung varietas Srikandi Kuning dan kedelai varietas Grobongan lebih adaptif pada lahan kering Kabupaten Parigi Moutong. Pola tanam yang memberikan hasil dan pendapatan terbaik adalah: kacang tanah - jagung dengan nilai B/C 2,04 dan 1,91 dengan MBCR 4,95 disusul pola tanam kacang tanah - kacang tanah dengan B/C 2,04 dan 1,59 dengan MBCR 6,71 dan meningkatkan pendapatan masing-masing sebesar 66,50% dan 21,0% dibandingkan dengan pola petani. Kata kunci: Lahan kering, varietas unggul, pola tanam, produktivitas dan pendapatan